The China dream how the aspirations of government, business, and people are driving the greatest transformation in history - Krane, Jonathan (Dallas Matt Holt Books, 2022)
The China Dream is your guide to understanding China's unmatched economic growth and fully realizing its status as an essential element in any well-designed investment portfolio, global business and participation in the global economy
Includes bibliographical references and index.
Keywords: China--Economic conditions--2000-